The Political Communication Ethics of Traditional Dayah Ulema in Bireuen Regency, Aceh Province - Katimin; Syukur Kholil; Yusfriadi (Britain International for Academic Research (BIAR) Publisher, 2020)
The political journey of Aceh's traditional dayah ulema before, did not succeed in gaining public support in the two election periods, namely the 2009-2014 period and the 2014-2019 period. Supposedly, the politics of the Dayah ulema had the full support of the people of Aceh which incidentally were a majority Muslim. This phenomenon is influenced by various factors, including political communication. Regarding scholars as political communicators, ethics is the most important thing in determining political success. Therefore, it will be examined regarding the ethics of political communication of traditional Acehnese dayah scholars. This study uses a qualitative approach with reference to ethnographic principles. The purpose of this study is to reveal the ethics of political communication in Aceh's traditional dayah ulema in Bireuen District.The results showed that the ethics of political communication of Aceh's traditional dayah ulema in the district of Bireuen generally referred to efforts to preserve their religious status as heirs of the Prophet in the morality of al-karimah. The spirit of the cleric who made them a public figure and public opinion to attract public empathy, is considered to have used religion for political purposes. The assumption of using da'wah pulpit as a campaign media indicates that there is justification for the absence of ethical communication politics.